ANTESEDEN DAN KONSEKUEN JOB ENGAGEMENT - Martini Martini; Sri Sulistyaningsih (Anindyaguna Ekonobisnis : Jurnal Ekonomi dan Bisnis STIE Anindyaguna, 2020)
This study aims to determine the antecedent and consequence of job engagement. The populationused in this study were employee of PT. Kaltim Adhiguna Muatan which amounts to 123 people.Method of sampling technique in this study carried with sensus sampling. The analysis tool usedis the technique of path analysis. The results obtained in this study is the positive effect oforganizational support and leadership positive effect on job engagement. And job engagementpositive affect on employee performance.Keywords: job engagement, organizational support, leadership, employee performance